2001
DOI: 10.1302/0301-620x.83b2.11500
|View full text |Cite
|
Sign up to set email alerts
|

Tibiocalcaneal fusion for avascular necrosis of the talus

Abstract: Between 1994 and 1999, we treated six patients with avascular necrosis of the talus by excision of the necrotic body of the talus and tibiocalcaneal fusion using an Ilizarov frame. This was combined with corticotomy and a lengthening procedure. Shortening was corrected in all patients except two, who were over 60 years of age. All patients had previous operations which had failed. All achieved solid bony fusion, with five out of six having either a good or an excellent result. We conclude that this is an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 8 publications
0
46
0
Order By: Relevance
“…[7][8][9] Although this procedure minimises the need for shortening, instability of the hindfoot remains and often leads to a pseudarthrosis. 10 Tibiocalcaneal fusion appears to produce favourable functional results, but at the expense of shortening. Dennison et al 10 and Kovoor et al 11 reported tibiotalar or tibiocalcaneal fusion for patients with bone loss of the talus combined with callotasis using the Ilizarov technique, which makes these operations technically demanding.…”
mentioning
confidence: 99%
“…[7][8][9] Although this procedure minimises the need for shortening, instability of the hindfoot remains and often leads to a pseudarthrosis. 10 Tibiocalcaneal fusion appears to produce favourable functional results, but at the expense of shortening. Dennison et al 10 and Kovoor et al 11 reported tibiotalar or tibiocalcaneal fusion for patients with bone loss of the talus combined with callotasis using the Ilizarov technique, which makes these operations technically demanding.…”
mentioning
confidence: 99%
“…If osteonecrosis develops and is symptomatic, a modified Blair arthrodesis or tibiotalar arthrodesis has had reasonable success [15,16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…An established osteomyelitis of the talus may be resistant to treatment because it is composed almost entirely of cancellous bone and is largely devoid of blood supply after fracture through the neck. The preferred treatment in fractures complicated by infection is excision of the infected bone followed by arthrodesis [16,17,25] .…”
Section: Discussionmentioning
confidence: 99%
“…Tibiocalcaneal arthrodesis was introduced by Blair as a treatment for this condition [15] but has the disadvantages of loss of function and shortening of the limb [16, 17]. The procedure also requires a long recovery period and carries a considerable risk of pseudarthrosis [2, 3, 18], and a large amount of bone needs to be harvested when an iliac bone graft is used.…”
Section: Discussionmentioning
confidence: 99%